The Effect of Person Organizational Fit (PO-Fit) and Organizational Commitment on Employee Performance through Organizational Citizenship Behavior (OCB) as Intervening Variable (Case Study Of Bank BSI KCP Stabat Proklamasi) - Saragih, Noprillia Ramadhani; Lathief Ilhamy, Muhammad; Ikhsan Harahap, Muhammad (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
Based on the background of the problem formulation and research differences and phenomena that have emerged, this study aims to find out what is related between individual values ​​and organizational values ​​(Person Organization Fit) that have an impact on Organizational Citizenship Behavior (OCB) on employee performance and organizational commitment (organizational commitment) as intervening variables, by taking the research object at Bank BSI KCP Stabat Proklamasi. The population used in this study were all employees at Bank BSI KCP Stabat Proklamasi totaling 30 respondents based on this study using primary data so the data collection was carried out using descriptive analysis and regression analysis and MRA. The results of this study indicate that production on productivity is negative and significant for Bank BSI KCP Stabat Proklamasi for 30 respondents who are the object of this study. The research method used in this study is a quantitative research method and the research data was obtained using the census questionnaire technique, by using an open-ended questionnaire to the respondents directly.